2023
DOI: 10.1590/0034-7167-2022-0250
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac anxiety in the perioperative period of patients undergoing cardiac surgical procedures: an observational study

Abstract: Objective: to compare cardiac anxiety symptoms in patients undergoing coronary artery bypass graft and valve surgery repair in the preoperative period, on the day of hospital discharge and on the first return visit after hospital discharge. Methods: an observational study, carried out in inpatient units and in outpatient clinic of a university hospital. Data were collected through interviews. Cardiac anxiety symptoms were assessed using the Cardiac Anxiety Questionnaire. Results: we observed the effect of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…There was a significant improvement in depressive symptoms after 6 months of surgery to the preoperative baseline value. This was in line with the previous study, which found that anxiety and depressive symptoms declined after 6 weeks of surgery (Kazitani et al, 2022). Another study found that longer preoperative hospital stay was associated with higher anxiety scores (Jia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant improvement in depressive symptoms after 6 months of surgery to the preoperative baseline value. This was in line with the previous study, which found that anxiety and depressive symptoms declined after 6 weeks of surgery (Kazitani et al, 2022). Another study found that longer preoperative hospital stay was associated with higher anxiety scores (Jia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%

Nursing Care for Patients Undergoing Heart Surgery

Leal Nascimento,
Silva Oliveira,
Sybelly Silva Matos
et al. 2024
hs